The effect of propofol and alfentanil on the increase in intraocular pressure due to succinylcholine and intubation - UMUROĞLU, TÜMAY (WICHTIG EDITORE, 2000)
PURPOSE. The aim of this study was to evaluate the effects of propofol and alfentanil on the increase in intraocular pressure (IOP) due to succinylcholine and intubation, in comparison with thiopental sodium and vecuronium bromide. METHODS. Forty patients aged 20-50 years, scheduled for elective surgery requiring endotracheal intubation, were assigned to four groups of ten. General anesthesia was induced with 2.5 mg/kg propofol in Group 1, 2.5 mg/kg propofol and 10 mu g/kg alfentanil in Group II and 5 mg/kg thiopental in Groups III and IV muscle relaxation was obtained with either 1.5 mg/kg succinylcholine (Group I, II and III) or 0.1 mg/kg vecuronium bromide (Group IV). In all patients mean arterial pressure, heart rate, oxygen saturation and IOP were recorded before (baseline) and after induction, after the muscle relaxant and after endotracheal intubation. RESULTS. Compared with their baseline values in Group I IOP decreased significantly after propofol (p<0.01) and increased significantly after intubation (p<0.01). In Group II IOP decreased significantly after propofol and alfentanyl (p<0.001), remained low after succinylcholine (p<0.01) and did not change after intubation. In Group III IOP decreased significantly after thiopental (p<0.001) and increased significantly after intubation (p<0.001). In Group IV ii decreased significantly after thiopental (p<0.001), remained low after vecuronium (p<0.001) and increased significantly after intubation (p<0.05). CONCLUSIONS. In all Groups, IOP did not increase significantly after succinylcholine, but only anesthesia induced with propofol and alfentanil prevented the increase in IOP due to intubation.
Keywords: intraocular pressure; propofol; alfentanil; succinylcholine; intubation; TRACHEAL INTUBATION; SUXAMETHONIUM; ANESTHESIA; VECURONIUM